Model Pendidikan 'Aqīdaħ di Kelas VII Madrasah Tsanawiyah Pondok Pesantren Modern Al-Ihsan Baleendah Bandung (Studi Deskriptif Tahun Ajaran 2013/ 2014) - Rahmawati, Ema (2014)
Pendidikandalamartiluasadalahsegalapengalamanbelajar yang dilaluipesertadidikdengansegalalingkungandansepanjanghayat.Pendidikandalambatasan yang sempitadalah proses pembelajaran yang dilaksanakan di lembagapendidikan formal. Di antarakomponenpentingdalampendidikanadalahtujuanpendidikan.BerkenaandenganrumusantujuanpendidikanIslām, DjawadDahlan (1993: 10) berpendapatbahwadalamajaranIslāmterdapatduakonsep yang diajarkanolehRasūlullāh Saw.yangmaknanyamemilikikaitaneratdengantujuanpendidikanIslām; yaitukonsepĪmāndanTaqwā.Dewasaini, pendidikanmatapelajaran'aqīdaħkurangdiperhatikanolehsebagianumatIslām.Kita patutmenyadaribetapapentingnyaperan'aqīdaħdalammenentukannasibbangsaini.Memeliharadanmemperkokoh'aqīdaħini pun hendaklahdibina di atasdasarimān yang kukuh, yang diperkuatdenganilmudanamalsalehsertadipeliharadaripenyelewengandankesesatan.Seorangmuslim yang memiliki'aqīdaħ yang kuatakanmenampakkanhidupnyasebagaiamalsaleh.Dalampenelitianini, penulismenggunakanpendekatankualitatifdenganmetodedeskriptif.Pertimbanganpenggunaanmetodeinilebihdiarahkanpadaupayamendeskripsikansuatufenomena yang terjadidanditemukanselama proses Pendidikan'aqīdāhmelaluimatapelajaran'aqīdaħakhlāq yang berlangsungdi kelas 7 MTS PondokPesantren Modern Al IhsanBaleendah, Bandung. Melaluipenelitianini, penelitiakanlebihmenekankanpadahasilanalisismelaluipengamatan, wawancaradanstudidokumentasi yang terkaitdengantujuan, program, substansimateri, proses pembelajarandancaraevaluasimatapelajaran'aqīdaħyang dilaksanakan.Dari hasilpenelitiandiperoleh data bahwatujuanpendidikan'aqīdaħmelaluimatapelajaran'aqīdaħakhlāqyang ingindicapai di kelas 7 MTS Al IhsanBaleendah, Bandung diantaranya: siswamampuhidupdanbergauldimanasajamerekaberada, sertamenjadikan Kader Agama danbangsa yang berakhlāqAl-Karīmaħ. Program pembelajaran'aqīdaħ yang dirancangyaitu program pembelajaranberupamodel silabus yang sudahdidapatkandariKementrian Agama, pelajaranGontor, danaturan'aqīdaħ yang sesuaidengan'aqīdaħ-akhlāq.Substansimateripendidikan'aqīdaħdalammatapelajaran'aqīdaħakhlāq yang diajarkanmeliputi : Dasar dan Tujuan 'Aqīdaħ Islām, keimanan kepada Allāh melalui pemahaman sifat-sifat Nya, memahami Asmāul Ḥusnā, dankeimanan kepada malaikat-malaikat Allāh dan makhluk ghaib selain malaikat. Proses pendidikan'aqīdaħ yang dilaksanakan di kelasprinsipnyaselarasdenganapa yang tertulisdalamSilabus 'AqīdaħAkhlāq MTS, sedangkanevaluasipembelajaranpadamatapelajaran'aqīdaħakhlāq yang dilaksanakanyaituberupatestulisdanteslisan.Model pendidikan yang digunakanadalah model pendidikan formal. Education in a wide meaning are means all of learning experiences of a student in all of his or her surroundings and in his or her entire lifetime. But in a more specificmeaning, education means it is a learning process held in a formal institution of education. Specifically, education means learning process in formal institution. Education has many components. Among those components, one of the important is the purpose of education. In the theme of Islamic education Djawad Dahlan (1993:10) said that in there are two concepts taught by Rasūlullah SAW, which had a strong relation with the concepts of faith and worship to Allāh SWT. Recently, the subject of faith education has lack of attention from some of the muslim communities. But basically, we still have to realize the important role of the faith education to rule the way of this nation. To obtain and strengthen the faith has to be cultivated on a strong faith, strengthen by the knowledge and good attitude, and also has to be protected from the lost and mistakes. A muslim with the strong faith, will run his or her life as a long way to do kindness. In this research, I use the qualitative methode with descriptiveapproach. The consideration of using this method in to emphasize on my effort to describe a phenomena that I found and happened during my observation in 'aqīdaħakhlāqlearning process held in 7th graders at Al Ihsan Boarding School. Through this research, I will emphasize to the analytical results that I have from my, observation, interviews and documentation study that connected to the purposes, programs, the substanceof material givens, learning process and the evaluation of the aqidaakhlaq subject that held in 7th grader's students of Al Ihsan Boarding School. From the research that I did, I could understand that the purpose of the 'aqīdaħakhlāqsubject is to make the student able to live and make relationship wherever they will promising generation of Islam and the nation who had good islamic attitudes. The design of the 'aqīdaħakhlāqlearning program is based a form of syllabus from the Ministry of religion of Indonesia, from Gontor Islamic School, aqida rules which are relevant with aqida attitudes term. Main lessons of the program are explanation about the basic and goals of islamicaqida, faith to Allāhthrough the understanding of Allāh, understanding AsmāulḤusnā, and believes the angels and all unseen creatures of Allāh. Principally, the education processes are relevant with what has written in the syllabus. And for the evaluations themselves are writing test and oral test. And for the education model that has been used is the formal education model.